2001
DOI: 10.1093/humrep/16.9.1900
|View full text |Cite
|
Sign up to set email alerts
|

One versus two embryo transfer after IVF and ICSI: a randomized study

Abstract: Our results indicate that among women who have good quality embryos in their first IVF/ICSI, good treatment results can be achieved. They support the idea of changing embryo transfer policy towards one embryo transfer without any remarkable decrease in the success rate, while dizygotic twins can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
2
19

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(200 citation statements)
references
References 11 publications
11
168
2
19
Order By: Relevance
“…The study presented here used exclusively day 5 embryos and clearly demonstrates that acceptable pregnancy rates can be achieved using single embryo transfers in a relatively unselected population of IVF patients. This study confirms those conducted previously (Martikainen et al, 2001;Salumets et al, 2003;Tiitinen et al, 2001;Vilska et al, 1999) using day 3 embryos. Only one study ) has included cumulative pregnancy rate but unfortunately the data did not include the cumulative rate for those patients having two embryos transferred in their stimulated cycle.…”
Section: Discussionsupporting
confidence: 93%
“…The study presented here used exclusively day 5 embryos and clearly demonstrates that acceptable pregnancy rates can be achieved using single embryo transfers in a relatively unselected population of IVF patients. This study confirms those conducted previously (Martikainen et al, 2001;Salumets et al, 2003;Tiitinen et al, 2001;Vilska et al, 1999) using day 3 embryos. Only one study ) has included cumulative pregnancy rate but unfortunately the data did not include the cumulative rate for those patients having two embryos transferred in their stimulated cycle.…”
Section: Discussionsupporting
confidence: 93%
“…Several randomized controlled trials in Europe have demonstrated that eSET significantly diminishes twin gestations and yields comparable live birth rates in good prognosis patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…eSET was later performed on older women \36 years of age [26][27][28][29][30]. These studies found a decrease in the multiple gestation rate without a decrease in the pregnancy rate in each case.…”
Section: Discussionmentioning
confidence: 99%